2009
DOI: 10.1186/1472-6874-9-1
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive tract infections in women seeking abortion in Vietnam

Abstract: BackgroundWomen requesting abortion are at increased risk of developing RTI complications. However, RTI control in many resource-poor countries including Vietnam have been faced with logistical and methodological problems due to lack of standardized definitions of RTIs, lack of well-validated diagnostic criteria, lack of accurate laboratory tests, and lack of diagnostic equipment and skills. This article investigates the prevalence of RTIs among Vietnamese abortion-seeking women, to evaluate the available diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 24 publications
4
21
4
Order By: Relevance
“…For trichomoniasis, the trend is similar, in that we found a 12.5% infection rate compared with the 0.3-3.3% from the other studies (Mallinson et al 2002;Rose et al 2005 andHng et al 2009), including 0.5% reported in the antenatal study from Tanzania. However, when comparing the infection rates between these studies one must be cognisant of the different diagnostic methodologies used in each of the studies (Table II).…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…For trichomoniasis, the trend is similar, in that we found a 12.5% infection rate compared with the 0.3-3.3% from the other studies (Mallinson et al 2002;Rose et al 2005 andHng et al 2009), including 0.5% reported in the antenatal study from Tanzania. However, when comparing the infection rates between these studies one must be cognisant of the different diagnostic methodologies used in each of the studies (Table II).…”
Section: Discussionsupporting
confidence: 86%
“…For gonococcal infection, the findings of the 4.5% in our study is much higher than the 0-1% reported by the other studies (Mallinson et al 2002;Rose et al 2005;Hng et al 2009;Msuya et al 2009). For trichomoniasis, the trend is similar, in that we found a 12.5% infection rate compared with the 0.3-3.3% from the other studies (Mallinson et al 2002;Rose et al 2005 andHng et al 2009), including 0.5% reported in the antenatal study from Tanzania.…”
Section: Discussioncontrasting
confidence: 70%
See 3 more Smart Citations